PENGARUH KONSERVATISME AKUNTANSI, FINANCIAL DERIVATIVE DAN KOMPENSASI RUGI FISKAL TERHADAP TAX AVOIDANCE - lisnawati; Sadewa, Prima (Jurnal Nusa Akuntansi, 2024)
This research aims to test and prove empirically the influence of accounting conservatism, financial derivatives and fiscal loss compensation on tax avoidance. This research was conducted on Consumer Non-cyclicals sector companies listed on the Indonesia Stock Exchange (BEI) in 2018-2022. The sample in the study used a purposive sampling method. This type of research uses a quantitative approach with an associative type, and there are 13 companies used as research samples with an observation period of 5 (five) years. The analysis technique uses multiple linear regression with a significance level of 0.05. The results of this research show that (1) accounting conservatism, financial derivatives and fiscal loss compensation have a simultaneous effect on tax avoidance, (2) Accounting conservatism has a positive effect on tax avoidance, (3) Financial derivatives have a positive effect on tax avoidance, (4) Compensation Fiscal losses have no effect on tax avoidance.